INVESTIGATING THE ENTREPRENEURIAL INTENTION OF FINAL-YEAR UNIVERSITY’S STUDENTS BY USING THEORY OF PLANNED BEHAVIOR (CASE: UNDERGRADUATE STUDENTS OF MANAGEMENT DEPARTMENT WIDYATAMA UNIVERSITY INDONESIA) - Utami, Sekar Indah; RS, Nataria Sari Yulius; Wijaya, Fahira Rachtia; Firdaus, Annisa; Pitaloka, Arachis Bentan; Nilasari, Irma (CENTRAL ASIA AND THE CAUCASUS, 2022)
Entrepreneurial intention arises because of a feeling of pleasure and a desire to be involved in risk-taking activities, to run a business or own business by taking advantage of existing business opportunities, and to create new businesses with innovative approaches. For Indonesia, which has a low number of entrepreneurships, increasing the number of entrepreneurs, especially among students, is very important. This study uses the Theory of Planned Behavior to determine the effect of attitude towards entrepreneurship, perceived behavioral control and subjective norm on entrepreneurial intention of final year students from the undergraduate Management Study Program at the Faculty of Economics and Business, Widyatama University, Bandung Indonesia. This research is quantitative research using a questionnaire for data collection. By using the Google-Form, 267 students were involved as respondents. The result of analysis using multiple regression shows that attitude towards entrepreneurship, perceived behavioral control, and subjective norms have a positive effect on entrepreneurial intention. Several recommendations have also been proposed.